Fatwa on satellite TV and the development of Islamic religious discourse. (1st November 2017) - Miladi, Noureddine; Karim, Saleh; Athambawa, Mahroof
Satellite TV and the Internet revolutions have reinvigorated religious discourse in public spaces. Across the world, religious TV channels and Internet religious websites have taken up the roles of traditional religious spaces such as churches, mosques, synagogues, gurdwaras and temples. Islamic religious content through fatwa (religious verdict) programmes and other online and satellite TV genre has attracted considerable attention over the last fifteen years. Such programmes have become influential platforms in constructing people's opinions. On Islamic-oriented satellite TV channels, fatwa provision has nowadays become a sophisticated phenomenon exceeding the traditional scope of religious teaching. To understand fatwa and its possible impact, it is necessary to gauge the plethora of platforms available for audiences and users as sources of understanding their religious needs starting with satellite TV programmes to the unlimited online platforms for the diffusion of their religious decree. This research attempts to understand the extent to which fatwa programmes on satellite TV and radio are significant in shaping people's opinion. Through the implementation of an extensive survey questionnaire on a sample of the Qatari society in addition to interviews with experts and religious scholars, findings show that fatwa on satellite programme can be very important in helping viewers better understand their religion. The results also indicated that respondents included in the survey showed apathy when it comes to the implementation of rulings coming from muftis on TV. In short, respondents may watch fatwa or religious programmes on satellite TV or they may listen to them on the Qur'an radio in Qatar but they do not necessarily consider them as totally authentic. Authentic scholarly views on matters of religious seem to be more credible when they originate from a reputable Imam whom they see face to face. Moreover, results show that satellite TV has facilitated the emergence of the pan-Arab mufti or global Faqeeh. It has also facilitated the emergence of independent muftis and freed fatwa from the official religious authorities in various countries.